Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1063/1.4895459
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of adipogenesis of mesenchymal stem cells by oscillating high-gradient magnetic fields and mechanical vibration

Abstract: Nowadays, the focus in medicine on molecular genetics has resulted in a disregard for the physical basis of treatment even though many diseases originate from changes in cellular mechanics. Perturbations of the cellular nanomechanics promote pathologies, including cardiovascular disease and cancer. Furthermore, whilst the biological and therapeutic effects of magnetic fields are a well-established fact, to date the underlying mechanisms remain obscure. Here, we show that oscillating high-gradient magnetic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…The magnetic forces that are exerted on the cell body are transmitted to the cell cytoskeleton and cell membrane. Even tiny mechanical forces that are slightly larger than the thermal fluctuation forces of less 1 pN (see Methods) can significantly affect cell functionality32495051.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic forces that are exerted on the cell body are transmitted to the cell cytoskeleton and cell membrane. Even tiny mechanical forces that are slightly larger than the thermal fluctuation forces of less 1 pN (see Methods) can significantly affect cell functionality32495051.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies indicate the crucial influence of external mechanical and magnetic forces on the cell shape, function and fate through physical interactions with the cytoskeleton network464956.…”
Section: Resultsmentioning
confidence: 99%
“…External loads can also be applied by acoustic waves, mechanical vibrations and microbubble cavitation, among others (Box S1). 7274 …”
Section: Manipulating Mechanobiologymentioning
confidence: 99%
“…The first study applied a low-frequency (1-10 Hz), high-gradient magnetic field and mechanical vibration to mesenchymal stem cells and showed that both mechanisms play an important role in F-actin remodeling and regulation of adipogenic differentiation. 37 The next two studies 38,39 incubated magnetic particles (iron oxide nanoparticles and permalloy microdisks, respectively) with cells in culture and applied AMFs. In the first one, 38 a hyperthermia-like field was employed (16 mT, 260 kHz), while in the second one, 39 a low-frequency field was used (9 mT, 20 Hz).…”
mentioning
confidence: 99%